Dietary Omega-3 fatty acids inversely associated with systemic inflammatory response index (SIRI): a population-based analysis of NHANES 2005–2018 - Liang, Xinglan; Luo, Liangqin; Lu, Juan; Xie, Xiaoying (Frontiers in Nutrition, 2025)
BackgroundOmega-3 fatty acids are known for their anti-inflammatory and antioxidant properties. However, the relationship between Omega-3 intake and the systemic inflammatory response index (SIRI) remains unclear. This study aimed to examine the potential association between Omega-3 fatty acid intake and SIRI.MethodsA cross-sectional study was conducted using comprehensive data from the National Health and Nutrition Examination Survey (NHANES) for 2005–2018, assessing total Omega-3 fatty acid intake and SIRI among adults. SIRI was calculated using the formula monocyte × neutrophil count/lymphocyte count. The total dietary intake of Omega-3 fatty acids was calculated by summing the intakes of docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA). Subgroup analysis, smoothed curve fitting, and segmented linear regression were employed to investigate the relationship between SIRI and Omega-3 fatty acid consumption across genders.ResultsA total of 26,416 participants were included in the study. Participants were classified into quartiles of Omega-3 fatty acid intake: 0–0.014, 0.015–0.037, 0.037–0.093, and 0.093–5.215. The participants’ SIRI ranged from 1.242 ± 0.916, with levels decreasing as Omega-3 fatty acid intake quartiles increased (Q1: 1.27 ± 0.88; Q2: 1.27 ± 1.01; Q3: 1.25 ± 0.91; Q4: 1.18 ± 0.87, P for trend < 0.001). In the fully adjusted model, total Omega-3 fatty acid consumption was negatively correlated with SIRI (β: −0.05; 95% CI: −0.09, −0.01). Subgroup analysis and interaction tests indicated no significant correlation between this negative association and age, sex, BMI, hypertension, diabetes mellitus, or coronary heart disease (p > 0.05 for all interactions). A “J”-shaped curve was observed in male participants, with an inflection point at 2.7 g Omega-3 fatty acid intake. On the left side of the inflection point, a negative correlation was observed (β: −0.07; 95% CI: −0.14, −0.00), whereas a positive and statistically significant correlation was found on the right side (β: 0.43; 95% CI: 0.05, 0.80; Logarithmic likelihood ratio test P = 0.014.ConclusionA negative association may exist between SIRI and the consumption of omega-3 fatty. Further extensive studies are still needed to analyze their interaction.